BRCA1 and BRCA2 germline mutations are frequently demonstrated in both high‐risk pancreatic cancer screening and pancreatic cancer cohorts. Issue 13 (15th April 2014) - Lucas, Aimee L.; Frado, Laura E.; Hwang, Caroline; Kumar, Sheila; Khanna, Lauren G.; Levinson, Elana J.; Chabot, John A.; Chung, Wendy K.; Frucht, Harold
<x xml:space="preserve">Abstract</x> BACKGROUND Approximately 10% of pancreatic ductal adenocarcinoma (PDAC) is due to a genetic predisposition, including the breast and ovarian cancer syndrome germline mutations BRCA1 and BRCA2. Knowledge of specific genetic mutations predisposing to PDAC may enable risk stratification, early detection, and the development of effective screening and surveillance programs. In the current study, the authors attempted to determine the diagnostic yield of testing for BRCA1/2 germline mutations in a PDAC screening cohort and a PDAC cohort referred for genetic testing. METHODS Patients in a high‐risk PDAC prevention and genetics program or those with a personal history of PDAC who were referred for genetic evaluation underwent testing for BRCA1/2 germline mutations. Clinical BRCA1/2 genetic testing included testing for the 3 Ashkenazi Jewish founder mutations or BRCA1/2 comprehensive testing. RESULTS A total of 37 patients without PDAC underwent BRCA1/2 testing at the study institution. Genetic testing identified 7 patients who were BRCA1/2 carriers for a yield of 18.9%. Six patients carried Ashkenazi Jewish founder mutations (3 with BRCA1 and 3 with BRCA2), and 1 patient was found to have a BRCA2 mutation on comprehensive testing. Thirty‐two patients with PDAC underwent BRCA1/2 genetic testing. Five patients had Ashkenazi Jewish founder mutations (2 with BRCA1 and 3 with BRCA2), and 2 patients were found to have BRCA2 mutations on comprehensive testing. The diagnostic yield was 7 of 32 patients (21.9%). CONCLUSIONS BRCA1/2 testing is useful in PDAC risk stratification and alters risk assignment and screening recommendations for mutation‐positive patients and their families. Clinical BRCA1/2 testing should be considered in patients of Ashkenazi Jewish descent with a personal history or family history of PDAC, even in the absence of a family history of breast and ovarian cancer. Cancer 2014;120:1960–1967. © 2014 American Cancer Society.